2015
DOI: 10.1097/mph.0000000000000418
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Craniospinal Irradiation for Pediatric Medulloblastoma Using VMAT and IMRT

Abstract: The use of both IMRT and VMAT provides good target tissue coverage and sparing of the adjacent tissue for MB. Both techniques resulted in OAR dose delivery within published pediatric dose guidelines, except those mentioned above. Pediatric patients with standard-risk MB remain at risk for late endocrinologic, sensory (auditory and visual), and brain functional impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Our dosimetric results were comparable to several dosimetric studies that have investigated highly conformal radiotherapy techniques such as IMRT, HT, or VMAT for CSI planning, most of which found that the use of VMAT, compared to conventional CSI, significantly reduces OAR doses while preserving good target coverage. With a 36 Gy dose and RapidArc technology, Fogliata et al.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our dosimetric results were comparable to several dosimetric studies that have investigated highly conformal radiotherapy techniques such as IMRT, HT, or VMAT for CSI planning, most of which found that the use of VMAT, compared to conventional CSI, significantly reduces OAR doses while preserving good target coverage. With a 36 Gy dose and RapidArc technology, Fogliata et al.…”
Section: Discussionsupporting
confidence: 79%
“…In comparing VMAT to IMRT, Al‐Wassia et al. found that compared to IMRT, VMAT had superior dose reduction to the eyes, lens and optic nerve, cochlea, heart, thyroid, brain, testes, uterus, breasts, and kidneys . By minimizing the dose to these OARs, VMAT would be able to theoretically minimize dose‐related long‐term complications such as neurocognitive decline, hearing and vision deficits, and endocrine dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…They were able to improve the coverage of the target area by using the VMAT technique, however, this did not result in significant differences. No remarkable differences were seen in terms of the dose exposures of the organs-at-risk between the two techniques 15 . These results were supported by other studies conducted at other institutes 16 − 18 .…”
Section: Sebestyén Et Al Demonstrated the Technique Utilized At Theimentioning
confidence: 82%
“…A new treatment strategy emerged with the introduction of the helical Tomotherapy (Accuray Inc, Sunnyvale, CA, USA) where large target volumes can be irradiated continuously and homogenously without field matching [ 13 , 18 , 20 , 27 , 28 , 29 ]. Additionally, HT is executed in supine position, which is favorable for nontarget tissue sparing, patient comfort, and dose conformity [ 30 , 31 , 32 ] with a homogenous dose distribution compared to 3DCRT [ 13 , 18 , 21 , 27 , 29 , 33 ].…”
Section: Introductionmentioning
confidence: 99%